2021
DOI: 10.1177/0008068321992520
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Estimation of a Scale Parameter of Bivariate Lomax Distribution by Ranked Set Sampling

Abstract: Ranked set sampling (RSS) is an efficient technique for estimating parameters and is applicable whenever ranking on a set of sampling units can be done easily by a judgment method or based on an auxiliary variable. In this paper, we assume [Formula: see text]to have bivariate Lomax distribution where a study variable [Formula: see text]is difficult and/or expensive to measure and is correlated with an auxiliary variable [Formula: see text] which is readily measurable. The auxiliary variable is used to rank the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…In addition, various authors have also demonstrated that the RSS gives more inferential efficiency than SRS from different perspectives (e.g., Almanjahie et al [10], Al-Omari et al [11], Yao et al [12], Aljohani [13]). For some recent contributions, one could also refer to the works of Koshti and Kamalja [14], Sabry and Shaaban [15] and Bhushan and Kumar [16] among others.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, various authors have also demonstrated that the RSS gives more inferential efficiency than SRS from different perspectives (e.g., Almanjahie et al [10], Al-Omari et al [11], Yao et al [12], Aljohani [13]). For some recent contributions, one could also refer to the works of Koshti and Kamalja [14], Sabry and Shaaban [15] and Bhushan and Kumar [16] among others.…”
Section: Introductionmentioning
confidence: 99%